Herbal Therapy for the Treatment of Acetaminophen-Associated Liver Injury: Recent Advances and Future Perspectives - Chang, Ling; Xu, Dongwei; Zhu, Jianjun; Ge, Guangbo; Kong, Xiaoni; Zhou, Ying (Frontiers in Pharmacology, 2020)
Acetaminophen (APAP) overdose is the leading cause of drug-induced liver injury worldwide, and mitochondrial oxidative stress is considered the major event responsible for APAP-associated liver injury (ALI). Despite the identification of N-acetyl cysteine, a reactive oxygen species scavenger that is regarded as an effective clinical treatment, therapeutic effectiveness remains limited due to rapid disease progression and diagnosis at a late phase, which leads to the need to explore various therapeutic approaches. Since the early 1990s, a number of natural products and herbs have been found to have hepatoprotective effects against APAP-induced hepatotoxicity in terms of acute liver failure prevention and therapeutic amelioration of ALI. In this review, we summarize the hepatoprotective effects and mechanisms of medicinal plants, including herbs and fruit extracts, along with future perspectives that may provide guidance to improve the current status of herbal therapy against ALI.